Benefits of surgical obturators in oral maxillofacial rehabilitation. Review of literature - Madelaine Bárbara Jiménez Gutiérrez; José Miguel Robaina Ruiz; Iván Díaz Cal (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Introduction: Fractures due to traumatic injury, surgical resection of tumors and congenital defects expose the maxilla to aggressions, and for rehabilitation there are obturator prostheses that recover some functions such as swallowing and phonation, as well as aesthetics. Objective: To summarize the benefits of the use of an obturator prosthesis as a rehabilitation form in Oral Maxillofacial Prosthesis services. Methods: Study of bibliographic review in 64 publications between 1978-2019 on the use of obturator prosthesis. 153 documents from the MEDLINE, PubMed and SciELO reference systems databases were consulted, screened and indexed on the Web of Sciences, Scopus, Redalyc and Latindex, with the use of the following descriptors: oral obturator, obturator prosthesis, oral cancer. Development: Prosthetic or palatal obturators are indicated to seal the surgically or congenitally exposed tissues of the oral cavity, and are a fundamental substitute for the hard palate, alveolar bone and surrounding soft tissues. During rehabilitation, the buccomaxillofacial prosthesis professional will make new modifications as the surgical site matures. The final prosthesis will have teeth similar to a dental prosthesis; the patient can remove and clean it, in addition to taking care of the hygiene of the defect. Conclusions: Prosthetic obturators correct palatal or maxillary defects, with various designs and attachments to be applied, which manages to recover a high level of quality of life for patients, since the oral cavity is separated from the nasal or sinus cavity, with a satisfactory dental and occlusal rehabilitation.